Investigation of new education methods using applied mechatronics - ERSOY, SEZGİN (Nova Publisher, 2011)
Explores the broad spectrum of science education with a focus on such topics as mechatronics, a multidisciplinary field combining mechanical engineering, electronics and computer technology; science education through research, science and technology museums as places for critical thinking.